1987
DOI: 10.1111/j.1475-1313.1987.tb01004.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Uses and Adverse Effects of Topical Administration of Atropine

Abstract: Atropine is used widely in the treatment of a variety of ocular conditions. This article reviews the uses of atropine in children and any adverse ocular or systemic side effects that have been reported after topical instillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…There is some suggestion in the literature of increased heart rate with injections of atropine 68 and a greater degree and duration of dilation with topical instillation of atropine 31,69 and Tropicamide, 30 and therefore some authors have suggested that cycloplegics in general are contra-indicated in DS. 70 However, there is no documented evidence of increased adverse reactions to topical Cyclopentolate, 71 although there may be a longer or greater pupil dilation. 72 We found an average dilated pupil size of 10 mm in our study population.…”
Section: Discussionmentioning
confidence: 97%
“…There is some suggestion in the literature of increased heart rate with injections of atropine 68 and a greater degree and duration of dilation with topical instillation of atropine 31,69 and Tropicamide, 30 and therefore some authors have suggested that cycloplegics in general are contra-indicated in DS. 70 However, there is no documented evidence of increased adverse reactions to topical Cyclopentolate, 71 although there may be a longer or greater pupil dilation. 72 We found an average dilated pupil size of 10 mm in our study population.…”
Section: Discussionmentioning
confidence: 97%
“…Some ophthalmologists prescribe progressive lenses, which may appear more attractive, but in our opinion it is impossible to ensure that children use the lower part of the lens, with the higher correction for near. Others prescribe miotic eye drops, which are not free from side-effects [5][6][7]. After the age of 10, it is possible to wean off bifocal lenses, gradually decreasing the correction of the near lens until it is totally eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…However, by 1971, the allegedly prolonged mydriatic effect of atropine in patients with Down syndrome had already been refuted 5 6. Moreover, since 1993, it has been understood that accommodation is inherently grossly diminished congenitally in approximately 80% of children with Down syndrome 7.…”
mentioning
confidence: 99%
“…Given the doses utilised in ophthalmic applications, concerns of systemic atropine toxicity are also unwarranted 5 6. One per cent ophthalmic solution contains 0.5 mg of atropine per drop, and 20 drops of atropine absorbed simultaneously via the conjunctiva would be necessary to reach the potential lethal dose for children 6 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation